Ischemic blood-brain barrier and Alzheimer's amyloid plaques development - Pluta, Ryszard (Henry Stewart Talks, 2008)
Ischemic blood-brain barrier involved in Alzheimer's amyloid plaques development and full-blown Alzheimer's disease, Brain ischemia starts Alzheimer's disease, Association and risk factors for Alzheimer's disease, Ischemic mechanisms in Alzheimer's disease in general